PERAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN DI KOTA TOMOHON - Kris Natalia Rante; Oktavianus Porajouw; Vicky R.B. Moniaga (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
The objective of this research is to describe the role of the agricultural sector in the economy of Tomohon City in 2005, 2010 and 2017. The research was conducted for 3 months starting from December 2018 - February 2019. The basic data used in this research is quantitative descriptive data. This data focuses on the problems that exist today, on actual problems. The data collected is first compiled, explained and then analyzed. The reserch result showed that the contribution of the agricultural sector to the economy of the city of Tomohon tends to decline, however, on the other hand the agricultural sector remains consistent in contributing to the economy of Tomohon City. This was indicated by the percentage contribution of the economic sectors to the Tomohon City GRDP in 2017, where the agricultural sector was the second largest contributor after the construction sector to Tomohon City GRDP so that it can be interpreted that the productivity of the agricultural sector in Tomohon continues to develop.Â Keywords:Â Role of agricultural sector, Economy, TomohonÂ City, Contribution